A rare complication of Crohn disease: Duodenocolic fistula - Bora, Gül; Sonbahar, Bilgehan Çağdaş; Özalp, Nejdet (Turkish Journal of Gastroenterology, 2017)
Abstract Crohn disease (CD) is a chronic inflammatory disease that may be observed in random areas of gastrointestinal tract. Fistula formation is common during the course of CD, whereas duodenocolic fistulas are very rare. It is possible to safely perform surgical resection in patients who have severe symptoms of duodenal fistula. In this study, we report a rare case of CD with duodenocolic fistula that has emerged from the previous surgical resection. Cite this article as: Bora G, Sonbahar BÇ, Özalp N. A Rare Complication of Crohn Disease: Duodenocolic Fistula. Turk J Gastroenterol 2017; 28: 498-501.